Corrosion Inhibition of Bark Extract of Euphorbia royleana on Mild Steel in 1M HCl - Thapa, Bishal; Gupta, Dipak Kumar; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2019)
The bark extract of Euphorbia royleana as a green corrosion inhibitor was studied in 1M HCl using weight-loss method and potential measurement. The results show that the bark extract of Euphorbia royleana is an effective anti-corrosion inhibitor of mild steel in acidic media. The corrosion rate decreases with the time of immersion. Weight loss experiment shows that the loss in weight decreases with the time of immersion and inhibition efficiency increases with the concentration of extract. It was observed that maximum inhibition efficiency is 99.60% in 100% concentration of extract. Potential measurement study shows that bark extracts act as a mixed type of inhibitor i.e. inhibits both anodically as well as cathodically.